2015
DOI: 10.1186/s12884-015-0781-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal death reviews at Bugando hospital north-western Tanzania: a 2008–2012 retrospective analysis

Abstract: BackgroundUnacceptably high levels of maternal deaths still occur in many sub-Saharan countries and the health systems may not favour effective use of lessons from maternal death reviews to improve maternal survival. We report results from the analysis of data from maternal death reviews at Bugando Medical Centre north-western Tanzania in the period 2008–2012 and highlight the process, challenges and how the analysis provided a better understanding of maternal deaths.MethodologyRetrospective analysis using mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 8 publications
11
15
0
Order By: Relevance
“…Documented recommendations or action plans in the MDSR systems were mostly directed to health facility (third delay) targeting directly health care provision such as knowledge and skills of health care providers. This seems to be reasonable as also other studies from Malawi, Tanzania, Kenya and Nigeria indicated that most maternal deaths occur due to substandard care in health facilities (29)(30)(31)(32)(33) while facility delivery in these countries stands at 91%, 63%, 61% and 39% respectively (21,(34)(35)(36).…”
Section: Comprehensiveness Of the Narrative Summaries And Action Planssupporting
confidence: 59%
See 1 more Smart Citation
“…Documented recommendations or action plans in the MDSR systems were mostly directed to health facility (third delay) targeting directly health care provision such as knowledge and skills of health care providers. This seems to be reasonable as also other studies from Malawi, Tanzania, Kenya and Nigeria indicated that most maternal deaths occur due to substandard care in health facilities (29)(30)(31)(32)(33) while facility delivery in these countries stands at 91%, 63%, 61% and 39% respectively (21,(34)(35)(36).…”
Section: Comprehensiveness Of the Narrative Summaries And Action Planssupporting
confidence: 59%
“…Most of these deaths occur in low resource countries both in and outside health facilities. Maternal death reviews have been done in a lot of countries including Tanzania, to reveal the causes and contributing factors to maternal deaths, with some success and challenges (2)(3)(4)(5)(6)(7). In 2015, Tanzania introduced the Maternal Death Surveillance and Response (MDSR) system in line with World Health Organization (WHO) recommendations (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Documented recommendations or action plans in the MDSR systems were mostly directed to health facility (third delay) targeting directly health care provision such as knowledge and skills of health care providers. This seems to be reasonable as also other studies from Malawi, Tanzania, Kenya and Nigeria indicated that most maternal deaths occur due to substandard care in health facilities (25)(26)(27)(28)(29) while facility delivery in these countries stands at 91%, 63%, 61% and 39% respectively (21,(30)(31)(32).…”
Section: Comprehensiveness Of the Narrative Summaries And Action Planssupporting
confidence: 59%
“…Most of these deaths occur in low resource countries. Maternal death reviews have been done in a lot of countries including Tanzania, to reveal the causes and contributing factors to maternal deaths, with some success and challenges (2)(3)(4)(5)(6)(7). In 2015, Tanzania introduced the Maternal Death Surveillance and Response (MDSR) system in line with World Health Organization (WHO) recommendations (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the routine MDSR system was less inclined to indicate such errors and did not report errors in management in most cases that led to death. Other studies have proposed that most maternal deaths occur due to delays in medical care while delays in seeking care are less important (23,(30)(31)(32)(33). Since Tanzania is seeing increased facility utilization and facility births, it is imperative for health care providers to identify substandard care that can be addressed to save lives (5).…”
Section: Identifying the Three Delaysmentioning
confidence: 99%